Food product preparation from the vinification of 'BRS Violeta' by-products - Nogueira, Tuany Yuri Kuboyama [UNESP]; Shimizu-Marin, Victoria Diniz [UNESP]; Gonçales, Ana Carolina [UNESP]; do Prado, Heloíza Ferreira Alves [UNESP]; da Silva, Roberto [UNESP]; Lago-Vanzela, Ellen Silva [UNESP] (FapUNIFESP (SciELO), 2023)
The objective of this work was to manufacture pizza dough, truffle, and cake using the paste of a by-product from the vinification of 'BRS Violeta' grape, as well as to determine some bromatological characteristics of these products. The by-product was pressed to remove excess must and crushed to obtain the paste. The paste, pasteurized at 80°C for 3 min and frozen at -18°C, was characterized for total phenolic compounds (TPC), total monomeric anthocyanins (TMA), and dietary fiber. The food products were characterized for the following parameters: moisture, energy value, and protein, lipid, ash, dietary fiber, total carbohydrates, and TPC contents. The contents found in the paste were: 326 mg GAE 100 g-1, for TPC; 185 mg mv35diglc 100g-1, for TMA; and 10 g 100 g-1, for dietary fibers. Based on the centesimal compositions of the food products, the pizza dough and truffle can be considered as a source of fiber and protein, respectively. The products show TPC contents between 51 and 63 mg GAE 100 g-1. It is possible to prepare food products of good nutritional quality, using grape by-product paste, to minimize waste in the field.
Elaboração de produtos alimentícios a partir de coproduto da vinificação da BRS Violeta
Keywords: by-product; circular economy; functional food; phenolic compound